2006
DOI: 10.1016/j.cnr.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The cellular response in neuroinflammation: The role of leukocytes, microglia and astrocytes in neuronal death and survival

Abstract: Neuroinflammation is a complex integration of the responses of all cells present within the CNS, including the neurons, macroglia, microglia and the infiltrating leukocytes. The initiating insult, environmental factors, genetic background and age/past experiences all combine to modulate the integrated response of this complex neuroinflammatory circuit. Here, we explore how these factors interact to lead to either neuroprotective versus neurotoxic inflammatory responses. We specifically focus on microglia and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
164
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(169 citation statements)
references
References 66 publications
2
164
0
3
Order By: Relevance
“…7A, the Epac agonist had a qualitatively similar effect on the mRNA levels of seven inflammatory mediators in resting microglia as had been previously shown for PGE 2 and butaprost (cf. Fig.…”
Section: Ep2 Activation Modulates Expression Of Inflammatory Mediatorsupporting
confidence: 75%
See 1 more Smart Citation
“…7A, the Epac agonist had a qualitatively similar effect on the mRNA levels of seven inflammatory mediators in resting microglia as had been previously shown for PGE 2 and butaprost (cf. Fig.…”
Section: Ep2 Activation Modulates Expression Of Inflammatory Mediatorsupporting
confidence: 75%
“…However, in traumatic brain injury, mice deficient for IL-6 showed increased oxidative stress, decreased cell survival, and delayed wound healing, indicating that IL-6 might also be protective (50). Here, we show that PGE 2 and EP2 activation by butaprost exacerbates the induction of COX-2, iNOS, and IL-6, which should promote inflammation caused by microglial activation, in classically activated microglia.…”
Section: Volume 288 • Number 13 • March 29 2013mentioning
confidence: 61%
“…T cells exposed to antigen can cross the intact brain-blood barrier and migrate into the brain (19,20). It has also been shown that immunologic reactions occur in the brain in response to a number of processes that affect the CNS and spinal cord (21). These findings encourage the development of immunotherapy for lesions of the CNS and the identification of tumor antigens.…”
Section: Discussionmentioning
confidence: 96%
“…Neuroinflammatory mechanisms involving microglial activation, astrogliosis, and lymphocyte infiltration probably also contribute to the cascade of events leading to neuronal degeneration (Carson et al, 2006;Hirsch and Hunot, 2009;More et al, 2013) in several neurodegenerative disorders, such as AD, PD, HD, amyotrophic lateral sclerosis (ALS) and progressive supranuclear palsy (Hirsch and Hunot, 2009;Wright et al, 2013). Exposure to lipopolysaccharides induces neuroinflammation in mice and dopaminergic neuronal cultures, which further leads to dopaminergic neuronal death and accumulation of insoluble cytoplasmic inclusions of α-synuclein in nigral neurons.…”
Section: Role In Glial Cell Regulated Neuronal Degenerationmentioning
confidence: 99%